Akibat Hukum Putusan Mahkamah Konstitusi Nomor 90/PUU-XXI/2023 Terhadap Sistem Demokrasi di Indonesia - Angel Lina, Angie; Bayu Aji, Alan (Jurnal Hukum In Concreto, 2024)
Indonesia is a constitutional state with a democratic system to implement the principle of popular sovereignty which runs based on the 1945 Constitution of the Republic of Indonesia. This article will examine the legal consequences of the Constitutional Court Decision No. 90/PUU-XII/2023 concerning the age limit for Presidential and Vice Presidential candidates regarding the democratic system in Indonesia. The research method used is normative juridical with a statutory approach, which takes data sources through primary legal materials and secondary legal materials. The research results show that the Constitutional Court Decision no. 90/PUU-XII/2023 has many irregularities which are not in accordance with the proper judicial review testing procedures. The Constitutional Court as an independent judiciary has the position to uphold law and justice. To maintain democracy, the Constitutional Court as a state institution has the power to exercise judicial power free from intervention by executive and legislative powers. However, the ruling that changes Article 169 letter q of the Election Law has given rise to controversy in Indonesia, especially in the atmosphere leading up to the 2024 general election. So the conclusion of this research is that there is an opening for intervention in decision making and conflicts of interests of constitutional judges in Constitutional Court Decision No. 90/PUU-XII/2023 is one of the factors in the decline of the current democratic system in Indonesia.